The Roles of Principals in Increasing Education Quality by Developing Teacher Profesionalism - Moh. Burhanudin (Didaktika Religia, 2017)
Education policy should be supported by educational actors (teachers) who are at the forefront. Efforts to improve the quality of education need to be done gradually based on the strategic plan. One of the efforts to improve teachers' professionalism is through the supervision of teaching. The principal in fostering teacher professionalism is by way of coaching, including (1) developing teachers’ knowledge by suporting them to persue higher education, (2) developing teaching strategy by helping them make learning device, and (3) developing teacher code of ethics by providing role model.